Implementation of AES-256 Algorithm for Encryption on Chatting Platforms - Nirwan, Saepudin; Hamidin, Dini; Azzalea, Shifa Eldita (Internet of Things and Artificial Intelligence Journal, 2024)
This research aims to design and build a web-based corporate chat media using prototype methodology and AES (Advanced et al.) algorithm for data encryption. The platform has been developed with MERN technology (MongoDB et al.), which allows the application to be dynamic and responsive. Prototype methodology is used for iterative development based on user feedback, ensuring the application meets user needs. The AES algorithm is applied to maintain the confidentiality and security of each message sent and received. The results show that the application effectively provides efficient and secure communication for the company, with an intuitive and easy-to-use interface. Implementing MERN technology provides flexibility in the development and maintenance of the application, making it the right solution for corporate communication needs.